The Plasminogen Activation System Modulates Differently Adipogenesis and Myogenesis of Embryonic Stem Cells - Hadadeh, Ola; Barruet, Emilie; Peiretti, Franck; Verdier, Monique; Bernot, Denis; Hadjal, Yasmine; Yazidi, Claire El; Robaglia-Schlupp, Andrée; De Paula, Andre Maues; Nègre, Didier; Iacovino, Michelina; Kyba, Michael; et al. (PLOS ONE, 2012)
Regulation of the extracellular matrix (ECM) plays an important functional role either in physiological or pathological conditions. The plasminogen activation (PA) system, comprising the uPA and tPA proteases and their inhibitor PAI-1, is one of the main suppliers of extracellular proteolytic activity contributing to tissue remodeling. Although its function in development is well documented, its precise role in mouse embryonic stem cell (ESC) differentiation in vitro is unknown. We found that the PA system components are expressed at very low levels in undifferentiated ESCs and that upon differentiation uPA activity is detected mainly transiently, whereas tPA activity and PAI-1 protein are maximum in well differentiated cells. Adipocyte formation by ESCs is inhibited by amiloride treatment, a specific uPA inhibitor. Likewise, ESCs expressing ectopic PAI-1 under the control of an inducible expression system display reduced adipogenic capacities after induction of the gene. Furthermore, the adipogenic differentiation capacities of PAI-1−/− induced pluripotent stem cells (iPSCs) are augmented as compared to wt iPSCs. Our results demonstrate that the control of ESC adipogenesis by the PA system correspond to different successive steps from undifferentiated to well differentiated ESCs. Similarly, skeletal myogenesis is decreased by uPA inhibition or PAI-1 overexpression during the terminal step of differentiation. However, interfering with uPA during days 0 to 3 of the differentiation process augments ESC myotube formation. Neither neurogenesis, cardiomyogenesis, endothelial cell nor smooth muscle formation are affected by amiloride or PAI-1 induction. Our results show that the PA system is capable to specifically modulate adipogenesis and skeletal myogenesis of ESCs by successive different molecular mechanisms.